Utilization of Hospital Solid Waste as Paving Blocks - Rini, Intan Dwi Wahyu Setyo; Lukman, Fadillah Afdalya; Gunawan, Adrian (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2024)
A hospital as a health facility has the potential to produce medical waste, which is harmful to the environment, if it is not handled properly and correctly. At Hospital X, infectious medical waste is chopped and sterilized at temperatures above 100oC using a sterilwave to reduce the size of the waste and hand it over to a third party at a substantial cost. This waste has the potential to be used as construction materials, such as paving blocks, which are used as parks in the hospital area. Therefore, this research was conducted to determine the best paving block mix design and composition using chopped medical waste as a fine aggregate substitution. In addition, this research carried out a TCLP test on paving blocks that had the best water absorption to find out whether paving blocks are good enough to strip potential soil contamination. The quality target for paving blocks in this study was to meet class D quality with a minimum compressive strength of 8.5 MPa and a maximum water absorption of 10%. The quality of compressive strength and water absorption was based on SNI 03-0691-1996, and the TCLP test referred to Indonesia Government Regulation Number 22 of 2021. The results showed that the mix design used is 1:5 for the ratio of cement and fine aggregate with an average compressive strength of normal paving blocks of 10 MPa. Whereas paving blocks with a mixture of medical waste with the best absorption were those with as much as 8% substitution of fine aggregate, with an average compressive strength value of 10 MPa. The results of the TCLP test on the best specimens showed that the levels of heavy metals in medical waste paving blocks met the TCLP A quality standards and were safe for use in hospital parks.